Infectiousness of HIV-Seropositive Patients with Tuberculosis in a High-Burden African Setting - Martinez, Leonardo; Sekandi, Juliet N.; Castellanos, Maria E.; Zalwango, Sarah; Whalen, Christopher C. (PloS one, 2016)
Policy recommendations on contact investigation of HIV-seropositive patients with tuberculosis have changed several times. Current epidemiologic evidence informing these recommendations is considered low quality, and few large studies investigating the infectiousness of HIV-seropositive and -seronegative index cases have been performed in sub-Saharan Africa. Objectives: We assessed the infectiousness of HIV-seropositive and -seronegative patients with tuberculosis to their household contacts and examined potential modifiers of this relationship. Methods: Adults suffering from their first episode of pulmonary tuberculosis were identified in Kampala, Uganda. Field workers visited index households and enrolled consenting household contacts. Latent tuberculosis infection was measured through tuberculin skin testing, and relative risks were calculated using modified Poisson regression models. Standard assessments of interaction between latent tuberculosis infection, the HIV serostatus of index cases, and other variables were performed.
Keywords: Mycobacterium tuberculosis; Household contacts; HIV; Tuberculosis infection; Infectiousness